Continuous professional development for madrasa teacher professionalism: engaging motivation for engagement - Tambak, Syahraini; Sukenti, Desi; Zabidi Abdul Razak, Ahmad; Agustina, Agustina; Amin Ahmad, Khalilullah; Firdaus, Firdaus; Syarif, Miftah (Institute of Advanced Engineering and Science, 2025)
Much research has been done on continuous professional development (CPD) madrasa (Islamic school) teachers, but incorporating motivation of engagement in future professions into them needs to be addressed. This study aims to determine CPD madrasa teachers based on the motivation to engage future professionals in teaching. This research used a phenomenological design involving 16 madrasa Aliyah teachers as informants. Data was collected by interviews with madrasa teachers and analyzed using a systematic design. This research shows that CPD madrasa teachers are related to organizing teaching and learning activities to improve teachers' abilities and competencies in carrying out professional duties and performing as educators. CPD should include skills using digital technology, ethics, and professional values, applying sharia principles, makarim sharia, and integrity in educating students. Madrasa teachers’ view of motivation for engagement in a future profession in CPD refers to the drive that teachers professionals have to continue to be committed to their profession and develop with the changes and demands of the times. The motivation for madrasa teachers’ future professional involvement and sustainable professional development is mutually reinforcing. Motivation becomes a driving force for madrasa teachers to engage in CPD, while CPD renews and strengthens madrasa teachers’ motivation by providing the skills and knowledge necessary to adapt to future challenges. In this way, motivation and CPD together support better quality education, increase job satisfaction for madrasa teachers, and ensure that teachers remain relevant and competent in facing developments in the world of education.